Development of STEM-PjBL Science e-Books to Improve Creative Problem Solving Skill of Junior High School Students - Rohmah*, Seffy Mufidatur; Rosana, Dadan; Mawaddah, Mutiara Ayu (Universitas Syiah Kuala, 2025)
21st century learning requires students to develop problem-solving skills with creative ideas. Identifying objects, formulating problems, exploring creative ideas and choosing the best solution are important skills in solving creative problems. STEM-PjBL learning integrated with the local potential of sand crackers is one alternative to improve their skills. The purpose of writing is to developing a STEM-PjBL model science e-books on temperature and heat material to improve students creative problem solving skills of junior high school students. The development model used is 4-D model, with stages including define, design, develop, and disseminate. The research subjects were students of class VIII MTsN 4 Kediri. Data collection was done through tests and non-tests (questionnaires, observations, interviews). The instruments used were product feasibility, validation sheet from material experts and media experts, instrument validation sheet, and practicality questionnaire. The results of the material validation and media validation are very good category with scores of 207 and 329 respectively. The percentage score of practicality questionnaire assessment is 93.9% and the score of the readability questionnaire assessment is 92.7%. The N-gain value of 0.46. It can be concluded that the STEM-PjBL science ebook developed effectively increases students' creative problem solving skill